'A space that worked for them': museum-based art psychotherapy, power dynamics, social inclusion and autonomy. Issue 4 (2nd October 2021) - Watson, Ellie; Coles, Ali; Jury, Helen
ABSTRACT: Background: This article focuses on art psychotherapists' experiences of using museum and gallery settings for group art psychotherapy. Aims: It aims to explore the impact of museum settings for group art psychotherapy on the dynamics of power between therapists and service users, and between service users and the wider community. Methods: Interview transcripts from five art psychotherapists working in museums were analysed using an interpretative phenomenological framework and arts-based methods. Results: Service users may feel valued and socially included by participating in art psychotherapy in museums and using museum objects can help service users to feel empowered within the therapeutic process. Museums offer service users choices, which can engender a sense of autonomy. A museum environment where therapists and service users explore together, and diverse perspectives flourish, may facilitate a flattening of hierarchies. This levelling of the potential power differential is enhanced by a sense of informality and human relating in these settings. Conclusions : The findings suggest that a museum environment for art psychotherapy can influence service users' experience of power and autonomy within the therapeutic relationship and within the wider social sphere. Implications for practice/policy/further research: Art psychotherapists may consider using museums to foster social inclusion, autonomy and a more equal sharing of power with service users, whilst it is recommended that art psychotherapy training courses teach about non-traditional practice and settings, such as museums, and power dynamics. Plain-language summary Sometimes art psychotherapy groups are run in museums and galleries rather than in traditional settings such as hospitals or community clinics. This article describes a research project exploring how using museums (including galleries with collections) for art psychotherapy groups can affect the group members. It focusses on how these museum environments can affect the power relationships between therapists and service users, and between service users and the wider community. Five art psychotherapists were interviewed about their work in museum settings. The data from the interviews was analysed using a variety of methods, including art-based methods. The research found that museum-based art psychotherapy can affect power relationships between therapists and service users and the wider community in several ways. Service users may feel more valued by being in a museum than in a more usual therapy setting, and connecting with museum objects can help facilitate the therapy process. Museums provide people with choices about how they want to interact with the collections and to move through the spaces. Therapists and service users can explore alongside each other and a wide range of responses can be expressed and experienced, helping to encourage a sense of equal worth. Finally, a sense of informality in a museum setting and its connection to the community can also help to level the power difference between therapists and service users. The article encourages art psychotherapists to explore using museums in their practice to encourage a more equal power relationship between therapists and service users, and to help service users to feel valued and socially included. It also encourages art psychotherapy training courses to include teaching about power dynamics and the use of museums. It suggests that more research into certain aspects of museum-based art psychotherapy identified in this research, such as increased informality and humour, would be valuable.